DISKRESI (FREIES ERMESSEN): PERANGKAT HUKUM PENUNJANG PEMBANGUNAN - Murtir Jeddawi (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2017)
Implementation of development requires appropriate legal policy to avoid trapped in collusion, corruption and nepotism. However, it is not uncommon for state officials to hesitate to take a position with the reason "fear" is accused of corruption. As a result, development becomes impeded. Discretion is actually a legal basis that is safe to use, but the lack of understanding makes state officials do not use it. This paper tries to explain the discretion that is "Living Law" is with the intention that all parties understand.